2021
DOI: 10.1292/jvms.21-0227
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of systemic infection and host responses in chickens experimentally infected with <i>Salmonella enterica</i> serovar Gallinarum biovar Gallinarum

Abstract: Salmonella enterica serovar Gallinarum biovar Gallinarum (S. Gallinarum) is a hostspecific pathogen causing systemic infection in poultry, which leads to significant economic losses due to high mortality. However, little is known about the dynamic process of systemic infection and pathogenic characteristics of S. Gallinarum in chickens. In the present study, we developed an oral infection model that reproduces the pathology of S. Gallinarum and clarified the host immune response of the infected chickens. Chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…A previous study has reported that the most characteristic pathological lesions of fowl typhoid, such as hypertrophy, white lesions, and small necrotic foci, were observed in the liver of chickens (Ojima et al, 2021 ). In this study, we compared the pathological changes in the liver of chickens infected with wild-type and wecB ::Cm mutant strains.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study has reported that the most characteristic pathological lesions of fowl typhoid, such as hypertrophy, white lesions, and small necrotic foci, were observed in the liver of chickens (Ojima et al, 2021 ). In this study, we compared the pathological changes in the liver of chickens infected with wild-type and wecB ::Cm mutant strains.…”
Section: Resultsmentioning
confidence: 99%
“…We recently established an oral infection model and investigated the pathogenic characteristics and dynamic process of S . Gallinarum-induced systemic infection in vivo , mimicking the natural infection in chickens (Ojima et al, 2021 ). In this study, to reveal the pathogenic mechanism and understand the biological function of ECA of S .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations